Legacy of the Kanun as Cultural Schema: A Linguistic-Anthropological Analysis for Contemporary Albanian Social and Heritage Education - Kosteri, Anisa; Lazri, Karmen (European Journal of Social Science Education and Research, 2025)
This study presents a linguistic-anthropological analysis of Father Fabian Barcata’s novel Lule (1924) as a historical ethnographic source for understanding the enduring legacy of the Kanun in contemporary Albania. The paper reframes the novel from a purely historical artifact into a pedagogical tool for social and heritage education. It addresses a critical gap in current research by examining how the cultural schemas of honor (nder), gender, and justice, embedded in the Kanun and vividly depicted in the novel, continue to inform modern social attitudes and present challenges for civic education. Through a critical discourse analysis of Barcata’s narrative, the study demonstrates how historical literature can be used to deconstruct and critically assess the persistence of traditional norms. The findings argue that engaging with such texts in educational settings is crucial for fostering cultural memory, promoting gender equality, and navigating the complexities of legal pluralism in a post-communist society that aspires to European integration.